Cadmium sulfide quantum dots impact Arabidopsis thaliana physiology and morphology. (February 2020) - Marmiroli, Marta; Mussi, Francesca; Pagano, Luca; Imperiale, Davide; Lencioni, Giacomo; Villani, Marco; Zappettini, Andrea; White, Jason C.; Marmiroli, Nelson
Abstract: The differential mechanisms of CdS QDs (Quantum Dots) and Cd ion toxicity to Arabidopsis thaliana (L.) Heynh were investigated. Plants were exposed to 40 and 60 mg L −1 for CdS QDs and 76.9 and 115.2 mg L −1 CdSO4 ·7H2 O and toxicity was evaluated at 5, 20, 35 (T5, T20, T35) days after exposure. Oxidative stress upon exposure was evaluated by biochemical essays targeting non-enzymatic oxidative stress physiological parameters, including respiration efficiency, total chlorophylls, carotenoids, ABTS and DPPH radicals reduction, total phenolics, GSH redox state, lipid peroxidation. Total Cd in plants was measured with AAS. Root and leaf morphology and element content were assessed in vivo utilizing low-vacuum Environmental Scanning Electron Microscopy (ESEM) with X-ray microanalysis (EDX). This integrated approach allowed identification of unique nanoscale CdS QDs toxicity to the plants that was distinct from CdSO4 exposure. The analyses highlighted that CdS QDs and Cd ions effects are modulated by the developmental stage of the plant, starting from T20 till T35 the plant development was modulated by the treatments, in particular CdS QDs induced early flowering. Both treatments induced Fe accumulation in roots, but at different intensities, while CdS QDs was associated with Mn increase into plant leaf. CdSO4 elicited higher levels of oxidative stress compared with QDs, especially the former treatment caused more intense respiration damages and reduction in chlorophyll and carotenoids than the latter. The two types of treatments impact differently on root and leaf morphology. Graphical abstract: Image 1 Highlights: CdS QDs and Cd ion impact differently on A. thaliana morphology and physiology. CdS QDs damage mostly roots and induce early flowering. CdS QDs and Cd ion modulate Fe concentration in roots.